The Influence of Organizational Climate on Employee Commitment at PT. Persada Technical Media - Sidik, Riswan; Sugiarto, Abdi (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The purpose of this research is to determine and analyze the influence of organizational climate on employee commitment at PT. Media Teknik Persada. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 67 people taken using proportional sampling. The research results show that organizational climate has a positive and significant effect on employee commitment. This is shown by the T-count value of T-count of 8.633 > t table 1.66864, with a significance value of 0.000 < 0.05. The regression coefficient shows that if organizational climate is increased by 1 unit, employee commitment will increase by 0.311 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.527 or 52.70%, which indicates that organizational climate has a low influence on employee commitment, while the remaining 47.30% is influenced by other factors that have not been studied. Thus, partially, organizational climate has a positive and significant effect on employee work at PT. Media Teknik Persada. This identifies that improvements in the organizational climate can contribute to increased employee commitment.